Mechanism of introduction of quality management system at the enterprises of the construction industry: case of the Republic of Kazakhstan - Zhuman, Yeldar; Juman, Jappar; Makulova, Aiymzhan; Kalaganov, Bakhytbek; Tagay, Akkhozha; Bastarova, Uldar (Business, Management and Economics Engineering, 2024)
Purpose – The aim of the research was to apply the principles of the quality management system in order to establish a framework for implementing quality management practices within the construction industry. Research methodology – The study involved analysing the global experience of certifying enterprises according to ISO 9001 standards. The research used a qualitative approach, analysing QMS documentation, case studies, and literature to gain a comprehensive understanding of QMS implementation in established companies. Findings – It resulted in the development of a system model for introducing and implementing the quality management system in construction industry enterprises, following the ISO 9001 standard. Practical implications – The enterprises of the Republic of Kazakhstan are not exceptions from world practice, including the enterprises of the construction industry. However, there are few construction industry enterprises that would be certified according to quality management standards, including the ISO 9001 standard. Some do not have the financial and human resources to implement a quality management system, others lack understanding of where to start. Originality/Value – The study also focused on generalising and providing detailed insights into the processes involved in implementing the quality management system at construction industry enterprises.